Discovery of candidate functional non-coding mutations in acute myeloid leukemia using single-cell chromatin accessibility sequencing - Ming Zhu; Jiali Zhu; Zhijuan Zhu; Yiding Yang; Jinxian Dai; Hua Li; Nainong Li; Jialiang Huang (Communications Biology)
Abstract Mutations and gene rearrangements are crucial for the diagnosis and subtyping of acute myeloid leukemia (AML). However, the contribution of non-coding genetic variants, particularly those within cis-regulatory elements (CREs), to AML pathophysiology and heterogeneity remains poorly understood. In this study, we characterize the single-cell chromatin accessibility landscapes of 10 bone marrow samples from AML patients at diagnosis. Additionally, we develop eMut, an integrated computational pipeline for detecting, imputing, and functionally characterizing non-coding mutations in CREs at the single-cell level. Our analysis identifies 2878 potential somatic non-coding mutations, highlighting the extensive mutational heterogeneity in the non-coding genome of AML patients, with recurrent non-coding mutations displaying cell type-specific patterns. We show that mutated CREs are enriched with blood-related genetic variants, potentially linked to AML-associated genes, and harbor a higher abundance of functional CREs, suggesting their functional relevance in leukemogenesis. Importantly, we pinpoint candidate functional non-coding mutations that associate with alteration of target gene expression in AML. Collectively, our work provides a comprehensive resource of single-cell chromatin accessibility in AML and introduces an integrative approach to identify candidate functional non-coding mutations contributing to cellular heterogeneity in AML.